Kekonduksian Terma Filem Polimer Lut Sinar, OHP - Mat Yunus, W. Mahmood (Universiti Putra Malaysia Press, 1996)
A measurement of thermal conductivity of OHP (overhead projector) polymer films is reported. Thermal conductivity of PVC, 3M infra-red and triacetate films was measured using a simple, inexpensive home-made apparatus. The values obtained were: (0.567 ± 0.005) Wm-1K-1, (0.312 ± 0.005) Wm-1K-1, and (0.171 ± 0.005) Wm-1K-1. The thermal conductivity of mylar film was also measured and its value of (0.212 ± 0.005) Wm-1K-1 is in good agreement with figures previously reported. It has been shown that the heat resistance of polymer films is linearly dependent on the thickness of the film in accordance with the theory.